Identification of Neisseria Gonorrhoeae in Female Sexual Workers (FSW) Localized on Baai Island, Bengkulu City - Lenzu, Henrek Miko; Silviani, Yusianti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Sexually Transmitted Infections (STIs) pose a significant global health challenge, particularly among high-risk populations such as female sex workers (FSWs). Neisseria gonorrhoeae, a causative agent of gonorrhea, is a major concern due to its prevalence and transmission via sexual contact. This study aims to identify the presence of Neisseria gonorrhoeae in female sex workers (FSWs) at the Pulau Baai locality, Bengkulu City, and examine the correlation between infection rates and factors such as duration of work and frequency of client visits. A descriptive observational study with a cross-sectional design was conducted, involving 31 FSWs who participated in the study after providing informed consent. Samples were collected through vaginal swabs and examined using Gram staining to identify Neisseria gonorrhoeae. The findings revealed that 3.2% (1 out of 31) of the participants tested positive for Neisseria gonorrhoeae. Statistical analysis showed that the risk of infection increased with the duration of work, as well as the frequency of client visits. The study concludes that while the overall infection rate is low, the prevalence of Neisseria gonorrhoeae remains a concern in this high-risk group. Regular screenings and preventive measures, including consistent condom use, are recommended to reduce transmission among FSWs.